PERAN PROTOKOL KESEHATAN DALAM MEMPENGARUHI KEPUTUSAN PEMBELIAN KONSUMEN HYPERMART DIKOTA PEKANBARU: A Gender Perspective - Muhalida Zia Ibhar; Frinov Feldiko Ibhar (Distribusi - Journal of Management and Business, 2022)
One of the Covid-19 pandemic impacts in Indonesia is changing consumer behavior in making purchasing decisions. In this study, to see involves that occur according to gender in making purchasing decisions after implementing health protocols. The company's implementation of health protocols is a consideration for customers in choosing where they shop. Therefore, this study aimed to see the effect of health protocols on customer purchasing decisions from a gender perspective and conducted this research at Hypermart Pekanbaru. This study took a sample of 400 active customers. This research uses the purposive sampling method, and SEM (Structural Equation Modelling) analysis was used in this study. The results showed that female consumers agreed more with the implementation of the health protocol and had a higher average score than male consumers. Furthermore, this finding revealed a significant effect on implementing suitable health protocols on consumer purchasing decisions. The implementation of health protocols carried out by Hypermart can consistently improve consumer purchasing decisions. Thus, companies must view this health protocol as necessary for consumers during the COVID-19 pandemic, even though the costs incurred tend to be expensive.